Diabetic nephropathy and end-stage renal disease in a 28-year-old woman, or is it? - Mahmood, Zainab (BMJ Case Rep, 2021)
A 28-year-old Hispanic woman presented to the emergency department with pneumonia and bilateral pulmonary oedema, requiring admission to the intensive care unit. Additional history included type 1 diabetes mellitus, End Stage Renal Disease on haemodialysis and Hashimoto’s disease. On further diagnostic evaluation, she was found to have systemic lupus erythematosus (SLE) with overlap syndrome. The goal of this case report was twofold: to share our holistic investigative processes and to explore how racial identity and experiences play a role in health disparities present in SLE. The diagnostic process was difficult because of language and socioeconomic barriers our patient experienced. Additionally, SLE in the Hispanic population has only recently been researched, limiting specifics about presentation and disease course. In the Hispanic population, SLE has increased morbidity and mortality when compared with the Caucasian population. Thus, our patient’s case highlights the need for holistic practices when diagnosing patients, particularly in historically and presently marginalised identities.